A Conductive polylactic acid/polyaniline porous scaffold via freeze extraction for potential biomedical applications. Issue 2 (2nd April 2016) - Razak, Saiful Izwan Abd; Dahli, Farah Nuruljannah; Wahab, Izzati Fatimah; Abdul Kadir, Mohammed Rafiq; Muhamad, Ida Idayu; Yusof, Abdul Halim Mohd; Adeli, Hassan
ABSTRACT: This paper reports for the first time a simple yet effective method for fabricating a conductive and highly porous scaffold material made up of polylactic acid (PLA) and conducting polyaniline (PANI). The electrical percolation state was successfully obtained at 3 wt% of PANI inclusions and reached a conductivity level of useable tissue engineering applications at 4 wt%. In addition, preliminary bioactivity test results indicated that the protonating agent could form a chelate at the scaffold surface leading to good in-vitro apatite forming ability during biomimetic immersion. This new conductive scaffold has potential as a suitable biomedical material that requires electrical conductivity.